HEALTH RESORT DAN SPA DENGAN PENDEKATAN ARSITEKTUR TROPIS - Cathrine Aurellia Ivana; Affrilyno Affrilyno; Bontor Jumaylinda BR Gultom (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2023)
Changes in lifestyle with increasingly crowded routines make humans pay less attention to physical conditions that can cause stress. So that from this potential, the idea of planning a design that prioritizes